Popular culture and the civic imagination : case studies of creative social change - Jenkins, Henry, 1958-; Peters-Lazaro, Gabriel; Shresthova, Sangita (New York University Press, 2020)
"Popular Culture and the Civic Imagination" examines case studies of creative social change"--